2013
DOI: 10.3389/fphar.2013.00049
|View full text |Cite
|
Sign up to set email alerts
|

After the chemotherapy: potential mechanisms for chemotherapy-induced delayed skeletal muscle dysfunction in survivors of acute lymphoblastic leukaemia in childhood

Abstract: There is evidence that survivors of childhood cancers, such as acute lymphoblastic leukemia (ALL), have increased rates of long-term skeletal muscle dysfunction. This places them at higher risk of physical restriction and functional impairment as well as potentially contributing to observed increases in cardiovascular disease and insulin resistance in later life. The mechanisms underlying these changes in skeletal muscle are unknown but chemotherapy drugs used in treatment for ALL are strongly implicated. Norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 76 publications
3
49
0
Order By: Relevance
“…Another anticancer agent, doxorubicin, has recently been shown to cause a catabolic response in skeletal muscle through oxidative stress by elevating the serum levels of inflammatory cytokines, especially tumor necrosis factor (TNF), resulting in a loss of skeletal muscle mass leading to weakness and fatigue [28]. One study reported delayed skeletal muscle dysfunction in survivors of childhood acute lymphoblastic leukemia, in which repeated administration of combination chemotherapy drugs (e.g., vincristine, glucocorticoids, doxorubicin, methotrexate, asparaginase) was strongly implicated [29]. These findings suggest that chemotherapy could affect skeletal muscle loss.…”
Section: Discussionmentioning
confidence: 99%
“…Another anticancer agent, doxorubicin, has recently been shown to cause a catabolic response in skeletal muscle through oxidative stress by elevating the serum levels of inflammatory cytokines, especially tumor necrosis factor (TNF), resulting in a loss of skeletal muscle mass leading to weakness and fatigue [28]. One study reported delayed skeletal muscle dysfunction in survivors of childhood acute lymphoblastic leukemia, in which repeated administration of combination chemotherapy drugs (e.g., vincristine, glucocorticoids, doxorubicin, methotrexate, asparaginase) was strongly implicated [29]. These findings suggest that chemotherapy could affect skeletal muscle loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its non-specific and systemic mode of action, chemotherapy also elicits effects on healthy tissues causing the classic side-effects attributable to anti-cancer therapy including nausea, vomiting, cardio-toxicity, immune disorders, peripheral and axial neuropathy, hair and weight loss and debilitative fatigue (Greene et al, 1993; Zitvogel et al, 2008; Gilliam and St Clair, 2011; National Cancer Institute, 2012; Ariaans et al, 2015). These side-effects often limit treatment tolerability, efficacy and therapeutic options, sometimes leading to the cessation of treatment all together and ultimately reducing patient quality of life and prognosis due to the development of co-morbidities (Gilliam and St Clair, 2011; Scheede-Bergdahl and Jagoe, 2013; Argilés et al, 2015; Cheregi et al, 2015). Emerging evidence suggests that the skeletal muscle is also a target of chemotherapy-induced atrophy (Pfeiffer et al, 1997), weakness and fatigue (Gilliam and St Clair, 2011), dysfunction (Scheede-Bergdahl and Jagoe, 2013; Bredahl et al, 2016) and insulin resistance (Ariaans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These side-effects often limit treatment tolerability, efficacy and therapeutic options, sometimes leading to the cessation of treatment all together and ultimately reducing patient quality of life and prognosis due to the development of co-morbidities (Gilliam and St Clair, 2011; Scheede-Bergdahl and Jagoe, 2013; Argilés et al, 2015; Cheregi et al, 2015). Emerging evidence suggests that the skeletal muscle is also a target of chemotherapy-induced atrophy (Pfeiffer et al, 1997), weakness and fatigue (Gilliam and St Clair, 2011), dysfunction (Scheede-Bergdahl and Jagoe, 2013; Bredahl et al, 2016) and insulin resistance (Ariaans et al, 2015). These effects appear to be more pronounced when chemotherapy is administered in childhood, due to the hyperplastic and hypertrophic nature of skeletal muscle at this early stage of life and persist well into adulthood (Ness et al, 2007; Scheede-Bergdahl and Jagoe, 2013; Ariaans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Though data on muscular changes among survivors of childhood cancer are sparse, Scheede-Bergdahl et al have reviewed potential mechanisms of chemotherapy-induced skeletal muscle dysfunction in survivors of childhood ALL, noting impairments in muscle satellite cells, motor neurons, and muscle mitochondrial function that all contribute to reduced mobility and oxidative function. 50 …”
Section: Musculoskeletal Limitationsmentioning
confidence: 97%